Evaluasi Program Gerakan Literasi Sekolah di SD Negeri Kebondowo 02 - Yoni Eka Saputra; Agustina Tyas Asri Hardini (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research includes an evaluation research whose purpose is to determine and measure the implementation of the literacy movement program at SD Negeri Kebondowo 02 on the reading interest of students, in order to determine the follow-up. The model used in this research is the CIPP (Context, Input, Process, Product) model. Data collection techniques used in the form of observation, interviews, and documentation studies. Data analysis in this study includes data reduction, data presentation, and conclusions or verification. Based on the results of the research, the school literacy movement program at SD Negeri Kebondowo 02 went well because it could have a positive impact. The supporting infrastructure for the implementation of this program is also adequate. So with this research, it can be used as a reference in developing, improving, and or determining the follow-up of this program.